Racial and ethnic disparities in coronary, vascular, structural, and congenital heart disease. Issue 2 (19th May 2021) - Grines, Cindy L.; Klein, Andrew J.; Bauser‐Heaton, Holly; Alkhouli, Mohamad; Katukuri, Neelima; Aggarwal, Varun; Altin, S. Elissa; Batchelor, Wayne B.; Blankenship, James C.; Fakorede, Foluso; Hawkins, Beau; Hernandez, Gabriel A.; et al.
Abstract: Cardiovascular disease (CVD) remains the leading cause of death in the United States. However, percutaneous interventional cardiovascular therapies are often underutilized in Blacks, Hispanics, and women and may contribute to excess morbidity and mortality in these vulnerable populations. The Society for Cardiovascular Angiography and Interventions (SCAI) is committed to reducing racial, ethnic, and sex‐based treatment disparities in interventional cardiology patients. Accordingly, each of the SCAI Clinical Interest Councils (coronary, peripheral, structural, and congenital heart disease [CHD]) participated in the development of this whitepaper addressing disparities in diagnosis, treatment, and outcomes in underserved populations. The councils were charged with summarizing the available data on prevalence, treatment, and outcomes and elucidating potential reasons for any disparities. Given the huge changes in racial and ethnic composition by age in the United States (Figure 1), it was difficult to determine disparities in rates of diagnosis and we expected to find some racial differences in prevalence of disease. For example, since the average age of patients undergoing transcatheter aortic valve replacement (TAVR) is 80 years, one may expect 80% of TAVR patients to be non‐Hispanic White. Conversely, only 50% of congenital heart interventions would be expected to be performed in non‐Hispanic Whites. Finally, we identified opportunities for SCAI to advance clinical care and equity for our patients, regardless of sex, ethnicity, or race.